Analisis Urgensi Pengembangan Modul Bimbingan Karir dalam Membantu Perencanaan Pendidikan Lanjutan Siswa SMP - Aulia Rahmi; Megaiswari Biran Asnah (Journal on Education, 2023)
Career planning in junior high school students is usually related to further education planning. further education planning for grade IX students is to help them prepare for further education and be able to make further education choices that match their potential. Although further education planning is important, some students still face various problems related to further education planning. This study aims to analyze the importance of developing a career guidance module that can help junior high school students' further education planning. This research method uses literature study research. The results showed that it is important to develop a module based on the "Guidelines for career guidance services for guidance and counseling teachers/counselors in primary and secondary education units by the ILO (international labor organization). Based on this guide, it is important to develop material that is needed by students but has not been explained in the guide, condense the material and of course use explanations that are easily understood by students in grade IX junior high school or equivalent.